EVALUATION OF THE EFFECTIVENESS OF TREATMENT WATER EMULSIONS FROM OIL BY PHYSICO-CHEMICAL METHODS - VOZNIUK, MARTA; SHABLIY, TETYANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In this work the processes of treatment of water emulsions from oil with application of aluminum coagulants and activated carbon as a sorbent-clouding agent were investigated. These were coagulants such as aluminum sulphate Al2(SO4)3, aluminum hydroxide Al(OH)3 and aluminum hydroxide Al(OH)2Cl. Treatment of water emulsions was carried out with coagulants separately and in combination with activated carbon, and studies were conducted to determine the effectiveness of their separate and compatible use. It is determined that aluminum coagulants in doses of 2–50 mg/dm3 both separately and in combination with a sorbent provide a high degree of oil removal from emulsions. The level of water treatment reaches 97–99%. The use of activated carbon in doses of 5-100 mg/dm3 causes a linear decrease in the concentration of oil in water with an increase in the dose of the sorbent. Aluminum hydroxide (without sorbent) has the greatest efficiency in oil removal from water, as it ensures maximum reduction of oil concentration in both fresh and mineralized water. At the same time, the compatible application of aluminum coagulants with activated carbon is characterized by efficiency fluidity. This efficiency depends on the type and concentration of coagulant, dosed sorbent, as well as mineralization of the initial water. The greatest stable and linear combined effect is observed with the simultaneous use of aluminum sulfate and activated carbon in the treatment of fresh water, and aluminum hydroxochloride in combination with activated carbon in the treatment of highly mineralized water. The degree of water treatment reaches 98,6 –99,3%, and 99,1–99,8%, respectively. The results of this study show that the use of aluminum coagulants to extract oil from water solutions of various mineralization is appropriate and effective.